2022
DOI: 10.1200/jco.2022.40.6_suppl.003
|View full text |Cite
|
Sign up to set email alerts
|

Clinical results of PERICLES: A phase II trial investigating atezolizumab +/- radiotherapy for advanced squamous cell carcinoma of the penis.

Abstract: 3 Background: Patients (Pts) with advanced squamous cell carcinoma of the penis (aPeCa) have a poor prognosis (21% 2-year overall survival from moment of diagnosis) and high morbidity, due to progressive locoregional disease. Pre-clinical studies show high rates of infiltrating immune cells and high PD-L1 expression, suggesting that immunotherapy may be beneficial for these patients. In the PERICLES study, we assess the activity of atezolizumab (atezo) in aPeCa pts, with or without radiotherapy (RT) to contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 0 publications
0
15
0
1
Order By: Relevance
“…In the PERICLES phase 2 trial of atezolizumab ± radiotherapy to locoregional lymph nodes in advanced pSCC, 1‐year progression‐free survival (PFS) was only 12%. Interestingly, complete responses were observed in two patients with pulmonary metastasis, which again emphasizes a potential role for ICIs in subsets of patients 40 . A retrospective study on ICI outcomes in pSCC reported a clinical benefit of 14.3% along with a median overall survival and PFS of 8.2 and 1.9 months, respectively, consistent with poor responses that used an unselected ICI approach 41 .…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…In the PERICLES phase 2 trial of atezolizumab ± radiotherapy to locoregional lymph nodes in advanced pSCC, 1‐year progression‐free survival (PFS) was only 12%. Interestingly, complete responses were observed in two patients with pulmonary metastasis, which again emphasizes a potential role for ICIs in subsets of patients 40 . A retrospective study on ICI outcomes in pSCC reported a clinical benefit of 14.3% along with a median overall survival and PFS of 8.2 and 1.9 months, respectively, consistent with poor responses that used an unselected ICI approach 41 .…”
Section: Discussionmentioning
confidence: 72%
“…Interestingly, complete responses were observed in two patients with pulmonary metastasis, which again emphasizes a potential role for ICIs in subsets of patients. 40 A retrospective study on ICI outcomes in pSCC reported a clinical benefit of 14.3% along with a median overall survival and PFS of 8.2 and 1.9 months, respectively, consistent with poor responses that used an unselected ICI approach. 41 In a case series from a phase 2 basket trial, Hahn et al…”
Section: Jacob Et Al Conducted a Comprehensive Genomic Analysis Of 78mentioning
confidence: 72%
“…To our knowledge, only a weak response to chemotherapy plus EGFR blockade has been observed [20], and immune checkpoint inhibitors alone or combined with radiotherapy for advanced PSCC did not show satisfactory efficacy in the initial results of the PERICLES study [21]. Preclinical evidence showed that EGFR‐driven lung tumours presented with high PD‐L1 expression and an inhibitory tumour microenvironment, suggesting that the combination of EGFR blockade and PD‐1 inhibitors may be a promising strategy in tumour control and delaying drug resistance [22].…”
Section: Discussionmentioning
confidence: 99%
“…Recently presented results of PERICLES phase II trial (NCT03686332), which included 32 patients with advanced penile cancer treated with atezolizumab, an anti-PD-L1 monoclonal antibody, alone or associated with local radiotherapy, showed a 30% oobjective response rate among 10 evaluable patients for response by RECIST 1.1 (including two complete responses), but the trial did not reach the expected PFS, its primary endpoint. Immunotherapy-related grade 3 or 4 adverse events occurred in 9.4% of patients ( 30 ). Avelumab, another anti-PD-L1 antibody already approved for the treatment of advanced urothelial cancer, is also under investigation in penile cancer as maintenance (NCT03774901) or second-line therapy (NCT03391479) after chemotherapy.…”
Section: Immune Therapymentioning
confidence: 99%